Ventriloquial reflexivity: Exploring the communicative relationality of the ‘I’ and the ‘it’ - Meier, Frank; Carroll, Brigid (Human relations (New York), 2023)
Can an exploration of managers’ real-time organizational talk make way for a profoundly revised theory of reflexivity? Indeed, our analysis of the reflexivity literature reveals four significant points of contestation – the subject/object distinction, temporality, representation and agency – all of which revolve around the interplay of an ‘I’ (at least one reflexive agent) and an ‘it’ (something to be reflexive about). The focus of this inquiry lies in how the ‘I’ and the ‘it’ are constituted communicatively and what generates, sustains and animates them in interaction. Such interactions are sourced from a post-experience master programme for practising managers, thus providing naturally occurring data amendable to a ventriloquial analysis. We identify and demonstrate three types of reflexive moments: conflating, bifurcating and animating. We subsequently theorize these as instances of ventriloquial reflexivity, using the terms conflating, bifurcating and animating to express the different moments in which speakers co-orient to the communicative constitution of the ‘I’ and the ‘it’. Ventriloquial reflexivity allows us to explore reflexivity as an interactional and situated accomplishment, thus further pointing to how reflexive practices can be understood and enhanced.